Variation of problem-posing approaches to improve learning outcomes and problem-posing abilities of prospective mathematics teachers - Candiasa, I Made; Mertasari, Ni Made Sri; Sastri, Ni Luh Putu Pranena; Oya, Abas (Journal of Education and e-Learning Research, 2025)
This study explores the effectiveness of different problem-posing approaches in improving learning outcomes and problem-posing abilities among prospective mathematics teachers. This study employed a pre- and post-tests control group experimental design. The experimental group engaged in online and direct problem-posing, the comparison group used peer-assisted and direct problem-posing while the control group relied solely on direct problem-posing. Three classes were selected through purposive sampling as the sample with 32 students assigned to the experimental group, 30 students to the comparison group, and 31 students to the control group. A one-way multiple analysis of variance (MANOVA) was conducted to determine the effect of problem-posing variations on material mastery and problem-posing ability both separately and simultaneously. Findings indicate significant differences among the three groups. Online problem-posing serves as an effective preparatory stage before direct problem-posing allowing students to build confidence and reduce anxiety. Problem-posing ability was assessed across two dimensions, the ability to formulate and present problems. The study highlights that structured problem-posing approaches enhance learning outcomes and problem-posing abilities. These findings emphasize the importance of incorporating online and peer-assisted problem-posing strategies in mathematics education to support student engagement, critical thinking, and skill development.